TATBIQ AN-NAZARIYYAH AL-MA‘RIFIYYAH FI TA‘LIM AL-LUGHAH AL-‘ARABIYYAH BI AL-MADRASAH AL-MUTAWASSITAH AL-MUTA KAMILAH AL-FAJR MATARAM 2024-2025 - Zian Halimah; Nasarudin Nasarudin; Husnan Husnan (Universitas Islam Negeri Mataram, 2025)
This study examines the application of cognitive theory in teaching Arabic at SMP-IT Al-Fajar Mataram. The main problem lies in the effectiveness of cognitive theory and the accompanying challenges within the context of language instruction. The study aims to identify the forms of cognitive theory implementation and the obstacles faced by both teachers and students. A qualitative descriptive method was employed, using data collection techniques such as observation, interviews, and documentation. The results showed that the application of cognitive theory aligns with educational goals focused on meaning comprehension, knowledge construction, and active student engagement. However, its implementation still encounters several challenges, including variations in students’ cognitive abilities, limited time, lack of instructional media, low motivation, and difficulties in conducting higher-order thinking-based assessments. Therefore, the success of this theory’s implementation largely depends on the teacher’s creativity and the support of a collaborative learning environment.